PENERAPAN STRATEGI PRACTICE REHEARSAL PAIRS PADA MATA KULIAH SENI TARI DAN DRAMA DI UPGRIS - Prasena Arisyanto; Mei Fita Asri Untari; Riris Setyo Sundari (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
This study aims to measure student learning outcomes and analyze the character education process in dance and drama courses at UPGRIS PGSD Study Program through practice rehearsal pairs. The research method used is a quantitative-qualitative mixed method. The target of this research is focused on dance and drama lectures in the even semester 2017/2018. The research was conducted at the Elementary School Teacher Education Study Program, Faculty of Education, University of PGRI Semarang. There are 4 data collection techniques used in this study, namely observation, interview, questionnaire and document study. The data validity technique used is triangulation technique and source triangulation. Data analysis techniques use the Gain index formula for quantitative analysis, and analysis of learning concepts and character education for qualitative analysis.The results showed that the application of rehearsal pairs practice strategies can improve student learning outcomes in the appreciation of dance material by bringing Dolalak dance. Measurement of learning outcomes is done by Gain index and get the result of g = 1,02 or g bigger than 0,7 which is included in the high category. Increasing student learning outcomes are influenced by learning materials, learning methods, and student factors themselves. Students become more enthusiastic to practice outside of lecture hours because there are friends who become their study partners. The adoption of pairs of rehearsal practice strategies can also strengthen character education for students, including caring, cooperation, responsibility, and democratic character, which is strengthened through face-to-face lecture processes and independent training tasks.